2020
DOI: 10.14295/cs.v11i0.3339
|View full text |Cite
|
Sign up to set email alerts
|

Allometry and morphophysiology of papaya seedlings in a substrate with polymer under irrigation with saline water

Abstract: The availability and quality of the irrigation water are among the limitations for the development of agriculture in the semiarid. Aiming at gathering information on these limitations, this work aimed to evaluate the association between a water-absorbing polymer and water salinity in irrigation frequencies, as well as container volumes on the allometric and morphophysiological indices of seedlings of the papaya (Carica papaya) cultivar ‘Sunrise Solo’. The treatments were obtained from the combination between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This effect causes delay and reduction of seedling emergence under saline conditions (Bezerra et al, 2014;Sá et al, 2015;F. S. Oliveira et al, 2016) as observed in T. esculenta (Figure 3), in addition to promoting lower growth of seedlings of this species (Melo et al, 2017) and of other species such as, for example, P. edulis (Bezerra et al, 2014(Bezerra et al, , 2019, A. squamosa (A. R. Silva et al, 2018a,b), A. heterophyllus (Oliveira et al, 2017), Pistacia vera L. (Rahneshan et al, 2018), Carica papaya L. (E. C. Nascimento et al, 2020), Solanum lycopersicum L. (Shin et al, 2020). The leaf index of chlorophyll a in T. esculenta seedlings was not affected by the linear interaction between electrical conductivity of water and polymer, and there was no adjustment for salinity (F ≤ 1.43; p > 0.10).…”
Section: Effects Of Water Salinity and Polymermentioning
confidence: 78%
See 3 more Smart Citations
“…This effect causes delay and reduction of seedling emergence under saline conditions (Bezerra et al, 2014;Sá et al, 2015;F. S. Oliveira et al, 2016) as observed in T. esculenta (Figure 3), in addition to promoting lower growth of seedlings of this species (Melo et al, 2017) and of other species such as, for example, P. edulis (Bezerra et al, 2014(Bezerra et al, , 2019, A. squamosa (A. R. Silva et al, 2018a,b), A. heterophyllus (Oliveira et al, 2017), Pistacia vera L. (Rahneshan et al, 2018), Carica papaya L. (E. C. Nascimento et al, 2020), Solanum lycopersicum L. (Shin et al, 2020). The leaf index of chlorophyll a in T. esculenta seedlings was not affected by the linear interaction between electrical conductivity of water and polymer, and there was no adjustment for salinity (F ≤ 1.43; p > 0.10).…”
Section: Effects Of Water Salinity and Polymermentioning
confidence: 78%
“…(Melo et al, 2017). The increase in soluble salts, in addition to reducing the water potential and consequently hindering water absorption, causes specific toxic effects of the ions (Taiz, Zeiger, Møller, & Murphy, 2017) and, in excess, can change the concentration of chlorophyll (Rahneshan, Nasibi, & Moghadam, 2018;Shin, Bhandari, Cho, & Lee, 2020) and quantum kinetics (Baker, 2008), limiting the energy flow for CO 2 assimilation; as well as gas exchange (H. H. C. Nascimento, Santos, Freira, Silva, & Nogueira, 2015) and biochemical reactions in chloroplasts (Cruz, Coelho, Coelho, & Santos, 2017) resulting in allometric and morphophysiological changes (E. C. Nascimento et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations